Academic Awareness Dictionary of Cyber Security - Al-Shemarry, Meeras Salman; Alsaadi, Elham Mohammed Thabit; Altememe, Maha Sabri; Abbas, Azhar Ali (KJCT, 2025)
The advancement of technology has significantly simplified the process of searching for unfamiliar keywords on Google and other search engines. This development is more effective, but not better. This is due to factors such as device battery consumption, internet connection; time spent searching for a specific term, and others, which become apparent when utilizing search engines. Hence, the development an offline and regularly updateable Android dictionary application is crucial. The main objective of this project is to create an online dictionary to facilitate access to academic terms exclusively for cybersecurity concepts. With the help of dictionaries, students and researchers in particular can better understand their topics, improve their communication, and improve their ideas and information for any subject from other disciplines by understanding the meaning of terms correctly and understandably according to their field of circulation in the academic, governmental or industrial side.